A bibliometric analysis of COVID-19 research in Africa - Guleid, F; Oyando, R; Kabia, E; Mumbi, A; Akech, S; Barasa, E (Cold Spring Harbour Laboratory Press, 2021)
Background: The ongoing COVID-19 pandemic has led to an unprecedented global research effort to build a body of knowledge that can inform mitigation strategies. We carried out a bibliometric analysis to describe the COVID-19 research output in Africa.